Problems in the Implementation of Authentic Assessment in Akidah Akhlak Learning at MI Ar-Rahman - Triandiny, Tamara; Edis Aidilia; Alfina Ayu Rahmadianti; Abdurrahmansyah (The Future of Education Journal, 2025)
Akidah Akhlak learning is a crucial foundation in Islamic religious education at the madrasah ibtidaiyah level, aimed at shaping Islamic character from an early age. This study aims to identify the problems, expectations, and student responses regarding the implementation of authentic assessment in Akidah Akhlak learning at MI Ar-Rahman. The research employs a qualitative approach using a case study method. The population consists of all teachers and fourth- to sixth-grade students at MI Ar-Rahman, with a purposive sample involving teachers, the principal, and students. Data collection instruments include observation, semi-structured interviews, and documentation, analyzed using the Miles & Huberman model with triangulation techniques. The findings reveal that the main challenges relate to student characteristics, limited facilities, and teachers’ difficulties in designing assessment tools. However, teacher strategies such as material repetition, contextual approaches, and repeated evaluations were effective in enhancing student understanding. The study concludes the need to improve teacher competence and supporting facilities, as well as to strengthen collaboration between schools, parents, and the community to ensure the sustainable implementation of authentic assessment.